2020
DOI: 10.2196/17234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Facial Features of Patients With Cancer: A Deep Learning–Based Pilot Study

Abstract: Background Cancer has become the second leading cause of death globally. Most cancer cases are due to genetic mutations, which affect metabolism and result in facial changes. Objective In this study, we aimed to identify the facial features of patients with cancer using the deep learning technique. Methods Images of faces of patients with cancer were collected to build the cancer face image data set. A face … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…On a higher-technological scale, using a deep learning technique, researchers found that AI can help identify faces of patients with cancer from those without [ 126 ]. This promising finding, not currently in use, suggests that AI-based telemedicine tools have the future potential to assist patients and health care practitioners with cancer screening and improve screening accuracy.…”
Section: Opportunities and Solutionsmentioning
confidence: 99%
“…On a higher-technological scale, using a deep learning technique, researchers found that AI can help identify faces of patients with cancer from those without [ 126 ]. This promising finding, not currently in use, suggests that AI-based telemedicine tools have the future potential to assist patients and health care practitioners with cancer screening and improve screening accuracy.…”
Section: Opportunities and Solutionsmentioning
confidence: 99%
“…Recent work has demonstrated that under certain conditions individuals can be reidentified from seemingly anonymous MRI scan images [ 11 ]. Patients’ medical images have inadvertently appeared in Google image searches [ 12 ], and analysis of human faces can enable inferences about one’s health status [e.g., 13 20 ] and even one’s genomic information [ 21 ]. Understandably, many in and out of the precision health research community wonder whether the measures taken to ensure responsible stewardship of facial imaging and imaging-derived data are appropriate and adequate.…”
Section: Introductionmentioning
confidence: 99%
“…With AI technologies, machines can identify patterns too intricate for humans to identify and process quickly. AI techniques are widely used in areas such as natural language processing, speech recognition, machine vision, targeted marketing, and health care, including efforts to combat COVID-19 [96][97][98][99]. While technologies such as virtual reality, smart sensors, drones, and robotics could play a positive role in supporting health care professionals to cope with the pandemic [100][101][102], AI technologies are arguably most instrumental in addressing some of the most prominent issues health experts and government officials are faced with, ranging from pandemic surveillance to COVID-19 drug and vaccine development [103][104][105][106].…”
Section: Unique Capabilities Of Aimentioning
confidence: 99%